Understanding contradictory styles of policing - Tamayo Arboleda, Fernando León (Theoretical criminology, 2024)
Policing scholars have shown that logics of police governance that appear mutually exclusive can coexist in the same space and time. Within police institutions, we can find more military-like mindsets alongside democratic rationalities. We here present a novel theoretical perspective for understanding such coexistence. Instead of attempting to identify police rationalities by reference to organizational/structural factors such as subcultures, training, or firearms and other equipment, we show that contradictory logics of policing can coexist within the same force by differentiating policing's targets by space, temporality, and identity. To do so, we use the idea of “chronotope” to identify and understand how police officers decide between conflicting rationalities of policing.